Detachment levels of Colombian caribbean mud volcanoes - López- Ramos, Eduardo; González Penagos, Felipe; Rincón Martínez, Daniel Andrés; Moreno Gómez, Nestor Raúl (CT&F - Ciencia, Tecnología y Futuro, 2022)
Regional analysis of mud volcanoes demonstrates the regional extension of these processes in Northern Colombia. Mud volcanoes are active systems that manifest the characteristics of the underlying sedimentary sequences on the surface, as well as the presence of hydrocarbons. These may which provide information about the oil systems and the characterization of new migration paths. New data acquired during field geology studies, along with the evaluation of acquired aerial images by dron, allowed to observe variations in terms of morphology and neotectonic process, being distinctive between mud volcanoes formed in different structural domains. Mud volcanoes formed in areas of basement without thrust faults (back stop zone) are usually circular, connected to the basement by regional faults. Other mud volcanoes formed in older and younger deformed belts tend to present ellipsoidal shapes, with drainages patterns that suggest local stress fields associated with regional strike slip movements of major faults. The analysis of U/Pb ages in detrital zircons extracted from mud volcanoes and outcropping sedimentary sequences in the Colombian Caribbean, together with the analysis of foraminiferal and palynomorph faunas, suggest different levels of detachment. Clay mineralogy and geochemistry indicate that mud volcanoes formed in the back stop and the Northern part of the San Jacinto deformed belt have sludge material originated in sedimentary sequences with contributions from continental basement rocks, while the mud volcanoes located in the central and Southern parts of the studied area tend to show sediments provided from deepest stratigraphic levels, derived from less evolved magmatic sources (dioritic basements). Gas and water analysis obtained from studied mud volcanoes suggest that the old deformed belt, Paleocene accretionary wedge and back stop areas, have evidences of thermogenic oil systems, while in the domain of the younger deformed belt the tendency is to indicate evidences of microbial process.